A Statistical Study of Bank Clearings, 1875-1914 - Frickey, Edwin (The Review of Economics and Statistics, 1930)
THE present study is a continuation of that described in a preceding article.' The object of this earlier investigation was to obtain for as long a period as possible prior to the outbreak of the World War an index of business activity as indicated by the fluctuations in a monthly series of aggregate bank clearings based upon a representative group of cities.2 The first installment of the present article contains certain supplementary discussion regarding this aggregate clearings series; the second installment will deal with the analysis of monthly data for eighteen individual cities.